COMPARISON OF DIFFERENT FORMULATIONS OF VITAMIN D - Rashid, Hafiz muhammad Fahan; Syed, Uneeba; Ahmad, Zaheer; Chauhdary, Kbaa Khalil; Musharraf, Usman; Kumar, Suresh (Journal of Ayub Medical College Abbottabad, 2017)
Background: Vitamin D Deficiency (VDD) is responsible for a wide spectrum of clinical diseases and vitamin D deficiency prevalence is frightening in most parts of the world including Pakistan. Therefore, supplementations of vitamin D are used in the population at high risk for the prevention and the treatment of vitamin D deficiency. Vitamin D supplementation comes in various formulations both oral and intramuscular. Cholecalciferol is the most commonly used preparation which is given through these routes of administration. There is need to study the fact that how much vitamin D levels are raised after administration of these different formulations as this can be a pivotal factor in determining dosage and route of vitamin D3. Methods: This cross-sectional study conducted on 320 cases and compared the efficacy of various Vitamin D3 preparations in raising Vitamin D levels conducted in Department of Endocrinology and Metabolism, Services Hospital, Lahore from February to July, 2016. Blood serum was drawn for vitamin D level in the cases at the time of presentation and after treatment. Results: Three hundred & twenty patients were enrolled in study and divided into four groups (A, B, C, D). There was no significant difference between groups (A, B, C, D) in change in vitamin d levels after 3 months of treatment (p-Value 0.446). Conclusion: Different preparations of vitamin D are equally effective in raising vitamin D levels at 12 weeks. However, there is a need to conduct large scale studies to further validate these results. Keywords: Deficiency; Vitamin D; Administration; Dosage; Efficacy